Chromosomal genome assembly resolves drug resistance loci in the parasitic nematode Teladorsagia circumcincta. - Jennifer McIntyre; Alison Morrison; Kirsty Maitland; Duncan Berger; Daniel R G Price; Sam Dougan; Dionysis Grigoriadis; Alan Tracey; Nancy Holroyd; Katie Bull; Hannah Rose Vineer; Mike J Glover; et al. (PLoS Pathogens)
The parasitic nematode Teladorsagia circumcincta is one of the most important pathogens of sheep and goats in temperate climates worldwide and can rapidly evolve resistance to drugs used to control it. To understand the genetics of drug resistance, we have generated a highly contiguous genome assembly for the UK T. circumcincta isolate, MTci2. Assembly using PacBio long-reads and Hi-C long-molecule scaffolding together with manual curation resulted in a 573 Mb assembly (N50 = 84 Mb, total scaffolds = 1,286) with five autosomal and one sex-linked chromosomal-scale scaffolds consistent with its karyotype. The genome resource was further improved via annotation of 22,948 genes, with manual curation of over 3,200 of these, resulting in a robust and near complete resource (96.3% complete protein BUSCOs) to support basic and applied research on this important veterinary pathogen. Genome-wide analyses of drug resistance, combining evidence from three distinct experiments, identified selection around known candidate genes for benzimidazole, levamisole and ivermectin resistance, as well as novel regions associated with ivermectin and moxidectin resistance. These insights into contemporary and historic genetic selection further emphasise the importance of contiguous genome assemblies in interpreting genome-wide genetic variation associated with drug resistance and identifying key loci to prioritise in developing diagnostic markers of anthelmintic resistance to support parasite control.